The O'Malleys of Texas - Richards, Dusty (Richards, Dusty. O'Malley's of Texas., 2017)
During the Civil War, Texas Rangers Harp and Long John O'Malley patrol a vast, unguarded range, protecting the families of soldiers off fighting at the front. At war's end, the Rangers are disbanded, and the O'Malleys sign on with a cattle drive across the most treacherous and deadly stretch of the American frontier from Texas to Sedalia.